Imiquimod 3.75% for field‐directed therapy of actinic keratosis: results of a prospective case‐series study in Greece - Befon, Angeliki (Int J Dermatol, 2019)
BACKGROUND: Imiquimod 3.75% is a field‐directed treatment for actinic keratosis that can detect and treat clinical and subclinical lesions across an entire sun‐exposed field. The detection of subclinical lesions is evidenced by an increase in lesions to the maximum lesion count during treatment (L (max)). We report clinical outcomes for the first 15 patients treated with imiquimod 3.75% in daily clinical practice in Greece. METHODS: Fifteen patients with actinic keratosis lesions were treated with imiquimod 3.75% in an outpatient setting in two 2‐week treatment cycles separated by a 2‐week treatment‐free interval. Actinic keratosis lesions were counted before treatment, at the end of the first treatment cycle (Week 2; L (max)), and 2 weeks after the second treatment cycle (Week 8). Local skin reactions (LSR) were also evaluated at Weeks 2 and 8. RESULTS: The median baseline actinic keratosis lesion count was 25, which increased to a median L (max) of 29 at Week 2 and decreased to a median of 5 at Week 8. The median percentage and absolute reduction in actinic keratosis lesions from L (max) to Week 8 were 87% and 23%, respectively. Most of the LSR were mild‐to‐moderate in intensity at Week 2 and had resolved by Week 8. CONCLUSION: Imiquimod 3.75% effectively detected and cleared both the clinical and subclinical actinic keratosis lesions across the entire sun‐exposed field in this cohort of Greek patients. Treatment was well tolerated.